Sexually transmitted infections in privately insured adults with intellectual and developmental disabilities. (6th March 2019) - Schmidt, Elizabeth K; Hand, Brittany N; Simpson, Kit N; Darragh, Amy R
Aim: Individuals with intellectual and developmental disabilities (I/DD) may have an increased risk of sexually transmitted infections (STIs) due to limited sexual health education and higher rates of sexual abuse, yet little is known about the prevalence of STIs and STI testing in this population.Methods: This study compared national samples of privately insured individuals with (n = 25, 193) and without I/DD (n = 25, 193) on the prevalence of STIs and STI testing.Results: In multivariable models, individuals with I/DD were significantly less likely to have an STI diagnosis and no difference was found between groups on the odds of STI testing overall.Conclusion: Findings may, in part, be explained by fewer sexual experiences, increased supervision in social settings and delayed onset of sexual activity among those with I/DD.